Lifestyle habits, macronutrient intake, and obesity prevalence among adolescents in rural-periurban community senior high schools in the Ho municipality of Ghana - Akoto, Sheila; Tandoh, Marina Aferiba; Nsiah, Kwabena; Asamoah-Boakye, Odeafo; Annaful, Veronica Tawiah (Frontiers in Nutrition, 2022)
Background: Adolescence is a critical stage in the life cycle that presents a window of opportunity for the formation of lifetime habits or an aversion to childhood malnutrition effects. This study assessed the lifestyle habits, macronutrient intakes, and obesity prevalence among adolescents in some selected Senior High Schools in rural-periurban communities in Ho Municipality. Methods: A cross-sectional survey was conducted among 272 adolescents aged 13–19 years and attending senior high schools in the Ho Municipality of Ghana. Data on sociodemographic, physical activity levels, dietary habits, and anthropometrics were obtained. A body mass index (BMI) and waist circumference (WC) were determined, while a repeated 24-hour dietary recall was used to collect the dietary intakes of the participants. Results: The majority of the adolescents did not meet the Recommended Dietary Allowances (RDA) for calories (94.5%), dietary protein (68.8%), and fibre (91.5%). Adolescent boys consumed more calories (1,969.7±579.9 Kcal) on average than adolescent girls (1,658.0±458.7 Kcal) (p = 0.001). Overweight and obesity prevalence were 15.8% and 8.5%, respectively. About 90.4% of the adolescents did not meet the WHO recommended 150 minutes per week of physical exercise. On sedentary, 97.6% of adolescents spent half an hour to five hours per day watching television when at home. Breakfast was the most frequently skipped meal (47.9%), and 59.6% of adolescents consumed fast foods such as pizza, burgers, and ice cream one to three times per week. Adolescent girls also had higher odds of being overweight or obese compared with adolescent boys (AOR = 2.4, p = 0.094, 95% CI = 0.9-6.4). Adolescents who did not meet the RDA for calories had lower odds of being overweight or obese compared with those who did (UOR = 0.3, p = 0.045, 95% CI = 0.1-0.9). Conclusion: Poor dietary habits and intake, sedentary lifestyle, and obesity prevalence were observed among the adolescents. Being an adolescent girl was associated with obesity risk, while not meeting caloric intake showed a protective effect. Efficient and effective nutrition and lifestyle education programme should be promoted in communities to improve the dietary intake and lifestyle habits of adolescents.